Drivers of the beta diversity of spider assemblages in southern Brazilian temporary wetlands. (23rd October 2019) - de Ávila, Arthur C.; Pires, Mateus M.; Rodrigues, Everton N.L.; Costi, José A.R.; Stenert, Cristina; Maltchik, Leonardo
Abstract : 1. The composition of local assemblages is assembled by an interplay of species sorting, mass effects and dispersal limitation processes. The contributions of assembly processes to metacommunity structure can change with ecosystem type and specificities of the study area. Spider composition is influenced by environmental features such as habitat structure and climate, and also by spatial distances between patches. However, little is known about the roles of assembly processes in spider metacommunity structure in wetlands. 2. The beta diversity patterns of spider assemblages were assessed in 24 temporary wetlands distributed along a latitudinal gradient in southern Brazil. The study also assessed the individual correspondence of beta diversity (and its turnover and richness components) with dissimilarities in habitat structure and climate, as well as with geographic distances, using Mantel and partial Mantel correlation tests and multivariate correlograms. 3. Turnover was the most important component of spider beta diversity. Mantel tests detected significant correlations of spider beta diversity with habitat structure. Partial Mantel tests detected significant relationships only between spider beta diversity (and the richness component) and geographic distances. Additionally, spider composition was more similar than chance on smaller scales. 4. These results evidenced a complex interplay of assembly processes explaining spider metacommunity structure in temporary wetlands. Although species‐sorting processes associated with habitat structure were important in structuring local spider composition, mass effects and dispersal limitation across climatic zones played an important role on a broader scale. Abstract : Investigations on the community assembly of spiders have generally focused on terrestrial ecosystems. However, little is known about the role of assembly processes in the structure of spider assemblages associated with freshwater habitats. The beta diversity of spider assemblages was studied in temporary wetlands. The correspondence of beta diversity with dissimilarities in habitat structure, climate and geographic distances among wetlands was also assessed. A complex interplay of assembly processes explained spider metacommunity structure. Species‐sorting processes associated with habitat structure acted locally, whereas mass effects and dispersal limitation across climatic zones acted regionally.